Empowering outbound mobility students towards future talents: Universiti Putra Malaysia (UPM) experience - A. R., Suhaimi; H., Nadia Zawani; C. M., Hasfalina; R., Ras Afirina (GADING Journal for the Social Sciences, 2023)
Providing market-ready talent is challenging. Education needs changes to facilitate the current and future needs of market development in education, a growing and vibrant field. Previous studies have proven that international student mobility is one of the key changes for future education in higher learning institutions. This paper demonstrates the findings of international outbound mobility affecting future employability, career development, and marketability. It is a qualitative study in nature, and the Putra International Centre (i-PUTRA), Universiti Putra Malaysia, has been the chosen institution for this paper. Student Mobility Program provides opportunities and benefits to the students and the institutions. The results indicate that the outbound mobility is enough to maximize benefits for many students. Other factors influencing students to partake in mobility programs include verbal motivation. The study recommends students to enhance their full potential on equipping internationally oriented labor market as global citizen.